KEMAMPUAN MENULISKAN KEMBALI ISI DONGENG DENGAN BERBANTUAN MEDIA AUDIO VISUAL SISWA KELAS VII SMP NEGERI 4 SUTERA KABUPATEN PESISR SELATAN - Faulina, Mutiara; DN, UpitYulianti; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2014)
The problem of this research was the studentsâ ability in rewriting the tales by using audio visual media in class VII of SMP Negeri 4 SuteraKabupatenPesisir Selatan. This research was aimed at describing the studentsâ ability in rewriting the tales by using audio visual media in class VII of SMP Negeri 4 SuteraKabupatenPesisir Selatan. This was a quantitative research which used descriptive method. Based on the results of the research five conclusions were drawn. First, the studentsâ ability in rewriting the tales by using audio visual media for the first indicator (events/plots) was excellent (96,96) in which their average score was in the range of 96-100%. Second, the studentsâ ability in rewriting the tales by using audio visual media for the second indicator (characterization) was more than adequate (68,68) in which their average score was in the range of 66-75%.Third, the studentsâ ability in rewriting the tales by using audio visual media for the third indicator (settings) was more than adequate (86,85) in which their average score was in the range of 86-95%. Fourth, the studentsâ ability in rewriting the tales by using audio visual media for the first indicator (moral values) was more than adequate (71,71) in which their average score was in the range of 66-75%. Fifth, in the general, the average score of the the studentsâ ability in rewriting the tales by using audio visual media in class VII of SMP Negeri 4 SuteraKabupatenPesisir Selatan was good (81,56) in which their average score was in the range ofÂ  76-85%.